Evaluación meta-analítica sobre el impacto de scratch en el aprendizaje de la programación por computadora - Hablich Proaño, Juan José Ricardo (2019)
The present project aimed to find out whether programming learning is significantly improved when the visual programming language Scratch is used. In this sense, a meta-analysis was developed based on the most relevant works published on the subject. The methodology used was used to gather all the information related to the subject and to achieve the objectives proposed in the investigation. In relation to the meta-analysis, works related to the subject was collected, through the consultation of two bibliographic databases of high scientific impact, such as the Scopus catalog and the Web of Science. A total of 10 results obtained from 8 papers published in the period 2008 to 2019, were processed statistically according to the meta-analysis approach. The programming language R was used for the statistical processing of the data, which led to the obtaining of diverse forest graphs that summarize the impact of Scratch on the learning of programming, as well as other associated analyzes. As a result, it was confirmed that yes, Scratch has a positive impact on learning programming. The size of the global effect, defined as a standardized mean difference, was significant and equal to 0.56 with a confidence interval [0.19; 0.92] to 95%. It was also found that this effect size is not sensitive to most of the moderating variables defined, except for the duration of the intervention. Regarding the publication bias, the Egger asymmetry test showed that the sample of selected studies is heterogeneous in terms of results and, therefore, the existence of bias cannot be affirmed. Keywords: Scratch, Meta-analysis, Visual Programming Language, Computer programming learning.